Bactericidal effects of ozone at nonspermicidal concentrations. - Gradil, C (1995)
A study was conducted to assess the use of ozone (O3) to control pathogens or contaminants of concern to animal breeders and regulatory officials. In separate experiments, samples of fresh bovine semen and Pseudomonas aeruginosa, Escherichia coli, or Campylobacter fetus subsp. venerealis were diluted with antibiotic-free milk (10(6) sperm and 10(6) organisms/mL of diluted semen), exposed in the previous day to a constantly monitored level of 5, 10, 15, or 20 micrograms/mL of O3 for 3-5 min. After 10 min at 30 degrees C, sperm motility was assessed and the samples cooled to 5 degrees C. Two and 18 h after the beginning of cooling, aliquots of each semen sample were evaluated for motility and cultured for organisms. Reductions were observed in P. aeruginosa and E. coli colony counts of 2 logs, and in C. fetus of 5 logs, after exposure for 2 h to O3 at a concentration of 5 micrograms/mL that had a moderate effect on sperm motility (reduction of 20%). Fewer than 100 colonies, i.e., a 4 logs reduction of all bacteria, were counted after dilution with ozonized-treated milk at 20 micrograms/mL of O3. However, this concentration of O3 reduced sperm motility by 50% 10 min after dilution. The results of these experiments indicate that a concentration and exposure time to O3 can be selected to reduce P. aeruginosa, E. coli, and C. fetus in contaminated bull semen diluted with milk while having only minimal effects on sperm motility.